Peel-Off Mask Formulation for Facial Skin Protection Made from Active Carbon Quantum Dots From Rice Washing Water - Gani, Abdul; Nazar, Muhammad; Restiana, Dinda Lisma (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
Excessive exposure to ultraviolet (UV) rays can damage facial skin. Carbon Quantum Dots (CQDs) are active ingredients that can be formulated into peel-off masks needed to protect facial skin from UV exposure. This research aims to formulate a peel-off mask as facial skin protection made from the active ingredient CQDs from rice washing water, test the characteristics, and determine user responses to the product. The mask formulation is divided into five versions, namely F0 (without CQDs), F1, F2, and F3 (with CQDs added at concentrations of 2%, 4%, and 6%, respectively), and F+ (with added vitamin C). The resulting formulations were tested through physical tests, fluorescence using a UV lamp, and UV blocking tests. The test results for the five mask formulas showed a pH range of 4.5-5.6, stability over three weeks of storage, drying time within 27-30 minutes, homogeneity, viscosity ranging from 12,810-18,430 cPs, and spreadability ranging from 5.4-6.6 cm. The results of the organoleptic test using the one-way ANOVA test show that variations in mask formulas do not have a significantly effect on preferences for color, smell, texture, and general preferences. The results of the fluorescence test showed that there was luminescence in formulas F1, F2, and F3. UV blocking properties in the wavelength range 290-320 nm are shown in the formulas F1, F2, F3, and F+. Based on these tests, it can be concluded that the peel-off mask formulation with CQDs from rice wash water successfully produced a good peel-off mask product with a high SPF value, especially in formula F3.